Holocene variability in hydrology, vegetation, fire, and eolian activity in the Nebraska Sand Hills, USA - Schmieder, Jens; Fritz, Sherilyn C; Grimm, Eric C; Jacobs, Kimberly C; Brown, Kendrick J; Swinehart, James B; Porter, Stephen C (The Holocene, 2013)
This study combined multiple aquatic and terrestrial proxies, including diatoms, pollen, grain size, and bulk-sediment chemistry to reconstruct the history of three lake sites located in the central Sand Hills of Nebraska, USA. Long-term changes in effective moisture are evident at all sites, with significant changes occurring at ~6000, ~4000, and ~ 2000 cal. yr BP. Both aquatic and terrestrial indicators suggest that effective moisture was low between 10,000 and ~6000 cal. yr BP, and that this time interval was the driest period of the Holocene. The dominance of benthic and tychoplanktic diatom taxa indicates relatively shallow lake-level, high sand influx indicates moderately high eolian activity, and the pollen assemblage suggests xeric grasslands with abundant mud flats. About 6000 cal. yr BP, all three sites experienced an increase in effective moisture. Lake-level rise is indicated by increases in planktic and tychoplanktic diatoms relative to benthic taxa, while greater abundance of grass pollen and charcoal, and decreased eolian flux indicate stabilized dunes with dense vegetation sufficient to fuel local fires. A significant hydrologic shift recorded at all sites occurred at ~4000 cal. yr BP. This event was characterized by substantial lake-level rise, yet decreased grass cover and fire frequency, and increased eolian activity. Water-table rise may have been caused by a combination of factors including: (1) formation of dune-dams that blocked old drainage channels, (2) reduced grass cover and hence reduced evapotranspiration, and (3) changes in the frequency and duration of drought. The most likely cause(s) of the differential response of the terrestrial and aquatic systems at this time is not clear, none-the-less the late Holocene was not nearly as dry as the interval prior to 6000 cal. yr BP. The last ~2000 yr were characterized by several short-term fluctuations in lake level, including an interval of drought between 950 and 750 cal. yr BP, coincident with increased eolian activity during the latter part of the Medieval Climatic Anomaly.
Keywords: diatoms; drought; Holocene climate change; lakes; Nebraska Sand Hills; pollen